2010
DOI: 10.1007/s00264-010-1142-1
|View full text |Cite
|
Sign up to set email alerts
|

The lateral condyle index: a new index for assessing the length of the lateral articular trochlea as predisposing factor for patellar instability

Abstract: The central trochlea has been considered as the major location of dysplasia. The purpose of this study was to investigate the influence of the lateral trochlea on patellar stability and to establish a new method for measuring the lateral trochlea on sagittal magnetic resonance (MR) images. Twenty-eight knees of 23 patients suffering from lateral patellar subluxation (12 knees with radiological signs of central trochlear dysplasia) and of 46 patients without patellofemoral complaints (without central trochlear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 16 publications
3
36
0
Order By: Relevance
“…A fellowship-trained orthopedic surgeon with a special interest in patellofemoral pathologies performed all measurements, and the inter-rater reliability was performed with a senior resident in orthopedics surgery (see Table 1); a specialized musculo-skeletal imaging radiologist trained both investigators prior to study commencement. The femoral trochlea was analyzed using the following parameters: trochlear dysplasia according to Dejour,25 trochlear sulcus angle, trochlear facet ratio (medial/lateral), 26 trochlear dysplasia, 25 lateral trochlear inclination angle 27 (all measured on the most proximal axial image with full cartilaginous coverage of the trochlea), lateral condyle index, 28 and antero-posterior trochlear measurement (Figure 1). 29 The patellar height was measured using the Caton-Deschamp index (CD-I), the Insall-Salvati index (InSa-I), and the patellotrochlear index (PT-I) ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…A fellowship-trained orthopedic surgeon with a special interest in patellofemoral pathologies performed all measurements, and the inter-rater reliability was performed with a senior resident in orthopedics surgery (see Table 1); a specialized musculo-skeletal imaging radiologist trained both investigators prior to study commencement. The femoral trochlea was analyzed using the following parameters: trochlear dysplasia according to Dejour,25 trochlear sulcus angle, trochlear facet ratio (medial/lateral), 26 trochlear dysplasia, 25 lateral trochlear inclination angle 27 (all measured on the most proximal axial image with full cartilaginous coverage of the trochlea), lateral condyle index, 28 and antero-posterior trochlear measurement (Figure 1). 29 The patellar height was measured using the Caton-Deschamp index (CD-I), the Insall-Salvati index (InSa-I), and the patellotrochlear index (PT-I) ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Patellar cartilage defects are closely related to the geometry of the patellofemoral joint. Patellar height, patellar lateral facet width, patellar lateral facet ratio, sulcus depth, lateral patellar displacement, patellar epicondylar congruence angle, and abnormal length of the lateral condyle have been associated with chondromalacia patellae [6,10,11]. It has been reported that frequent recurrent dislocations, subluxations, and especially severe patellar femoral cartilage defects in the presence of patella alta also increase the presence of chondromalacia patellae [6,[12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In the other 17% had an abnormal isolated lateral trochlear height with normal central and medial heights. The lateral trochlea may also be shorter (in the sagittal plane), extending less proximally 38 and more parallel to the posterior condyle (in the axial plane), providing less lateral restraint than in patients without patellar dislocation. 39 Axial images are also used to measure the TT-TG distance and lateral patellar tilt.…”
Section: Radiographic Examinationmentioning
confidence: 97%